Prediction of Cardiovascular Disease by the Framingham‐REGICOR Equation in the High‐Risk PREDIMED Cohort: Impact of the Mediterranean Diet Across Different Risk Strata. Issue 3 (March 2017) - Amor, Antonio J.; Serra‐Mir, Mercè; Martínez‐González, Miguel A.; Corella, Dolores; Salas‐Salvadó, Jordi; Fitó, Montserrat; Estruch, Ramón; Serra‐Majem, Lluis; Arós, Fernando; Babio, Nancy; Ros, Emilio; Ortega, Emilio; et al.
Abstract : Background: The usefulness of cardiovascular disease (CVD) predictive equations in different populations is debatable. We assessed the efficacy of the Framingham‐REGICOR scale, validated for the Spanish population, to identify future CVD in participants, who were predefined as being at high‐risk in the PREvención con DIeta MEDiterránea (PREDIMED) study—a nutrition‐intervention primary prevention trial—and the impact of adherence to the Mediterranean diet on CVD across risk categories. Methods and Results: In a post hoc analysis, we assessed the CVD predictive value of baseline estimated risk in 5966 PREDIMED participants (aged 55–74 years, 57% women; 48% with type 2 diabetes mellitus). Major CVD events, the primary PREDIMED end point, were an aggregate of myocardial infarction, stroke, and cardiovascular death. Multivariate‐adjusted Cox regression was used to calculate hazard ratios for major CVD events and effect modification from the Mediterranean diet intervention across risk strata (low, moderate, high, very high). The Framingham‐REGICOR classification of PREDIMED participants was 25.1% low risk, 44.5% moderate risk, and 30.4% high or very high risk. During 6‐year follow‐up, 188 major CVD events occurred. Hazard ratios for major CVD events increased in parallel with estimated risk (2.68, 4.24, and 6.60 for moderate, high, and very high risk), particularly in men (7.60, 13.16, and 15.85, respectively, versus 2.16, 2.28, and 3.51, respectively, in women). Yet among those with low or moderate risk, 32.2% and 74.3% of major CVD events occurred in men and women, respectively. Mediterranean diet adherence was associated with CVD risk reduction regardless of risk strata ( P >0.4 for interaction). Conclusions: Incident CVD increased in parallel with estimated risk in the PREDIMED cohort, but most events occurred in non–high‐risk categories, particularly in women. Until predictive tools are improved, promotion of the Mediterranean diet might be useful to reduce CVD independent of baseline risk. Clinical Trial Registration: URL:http://www.Controlled-trials.com . Unique identifier: ISRCTN35739639.